Accessory Vein Obliteration Criteria for Immature Fistulae: A Modest Proposal for an Old Paradigm. Issue 5 (6th May 2014) - Haq, Naveed Ul; Albaqumi, Mamdouh
Abstract Venous stenosis and/or presence of accessory vein (av) are the two most common causes of early fistula failure. While treatment of stenosis is better defined, there are no clear criteria for obliteration of the av. Often, interventionalists rely on visual assessment of flow through the av and its diameter (significant if > 1/3 of the main fistula diameter) for intervention. The purpose of this study was to establish objective criteria for the management of av. Various computational fluid dynamics simulations were performed to analyze blood flow in the arteriovenous fistula (AVF). av of different diameters and angles was then added at various locations in the AVF and comparison of simulation results was undertaken. The computational model revealed that when the av was 33% of the diameter of the AVF, flow in av was only 7%. When diameter of the av was increased to 50% and 66% of the diameter of the AVF, flow through the av was 10% and 31% of the flow in main AVF, respectively. Location or angle of take‐off of av did not alter flow. This report provides objective information regarding criteria for av obliteration. It needs to be further validated in randomized clinical trials.